2021
DOI: 10.1002/ente.202100297
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Zn Deposition Achieved by Conductive Carbon Additive for Zn Anode in Zinc‐Ion Hybrid Supercapacitors

Abstract: The nonuniform zinc nucleation process on the surface of zinc metal anodes is known to result in irreversible dendrite growth, which brings the risk of short circuit for the zinc‐ion hybrid supercapacitor (ZIHS). Herein, a conductive carbon−zinc composite anode with dense active sites is reported to achieve controllable dendrite growth. This unique modified anode in the ZIHS enables extremely low polarization (47 mV) in the symmetric battery test and delivers excellent application performance (capacity retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…It can be found that whether at low current density and capacity or high current density and capacity, the cumulative capacity in this work is superior. It means that the method of inducing preferential growth of (002) plane by using BMIm + ion as an additive is very competitive with other methods, including optimizing the separator, [14,15] modifying coating layers, [16][17][18][19][20][21][22] using other additives, [11,[23][24][25][26][27][28] and processing/heating treatment of the Zn anode. [12,13,29] Besides, the rate performance (Figure S19, Supporting Information) of Zn||Zn symmetric cells cycled in Blank and 0.02 m BMIm + shows that the cell cycled in 0.02 m BMIm + can achieve extremely stable Zn 2+ plating/stripping behavior at various current densities (0.5-10 mA cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be found that whether at low current density and capacity or high current density and capacity, the cumulative capacity in this work is superior. It means that the method of inducing preferential growth of (002) plane by using BMIm + ion as an additive is very competitive with other methods, including optimizing the separator, [14,15] modifying coating layers, [16][17][18][19][20][21][22] using other additives, [11,[23][24][25][26][27][28] and processing/heating treatment of the Zn anode. [12,13,29] Besides, the rate performance (Figure S19, Supporting Information) of Zn||Zn symmetric cells cycled in Blank and 0.02 m BMIm + shows that the cell cycled in 0.02 m BMIm + can achieve extremely stable Zn 2+ plating/stripping behavior at various current densities (0.5-10 mA cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the preferential growth of ( 105), (103), and (002) planes can form a compact deposition layer to inhibit corrosion and H 2 evolution to a certain extent. [12,13] Therefore, reasonable manipulation of crystal orientation is of great significance for AZIBs.Up to now, the methods of manipulating crystal orientation in AZIBs mainly include optimizing the separator, [14,15] modifying coating layers, [16][17][18][19][20][21][22] using electrolyte additives, [11,[23][24][25][26][27][28] and processing/heating treatment of the Zn anode. [12,13,29] In the above methods, using electrolyte additives is much attractive because of its convenience and cost-effectiveness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pouch-type Zn8VOH full cell exhibited an impressive initial capacity of 18.7 mA h and a high capacity retention of 82.8% after 200 cycles. Both the cycling performance and rate capability of Zn8Zn symmetric cells are among the highest reported to date using different electrolyte additives to regulate the preferred crystallographic orientation, [22][23][24][25][26][27] highlighting the promising potential of the SPS additive for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the surface oxygen‐containing functional groups in carbon materials provide the surface with high zicophilicity, resulting in a reduction of the Zn nucleation overpotential and well‐dispersed Zn nuclei over the carbon surface. [ 46 , 47 , 48 , 49 , 50 ] The uniform Zn deposit morphology would be attributed to the oxygen‐containing surface defects (Figure S15 , Supporting Information) and the large surface area of the 3D structured CC.…”
Section: Resultsmentioning
confidence: 99%